2019
DOI: 10.1109/tbme.2019.2895683
|View full text |Cite
|
Sign up to set email alerts
|

A Scale Mixture-Based Stochastic Model of Surface EMG Signals With Variable Variances

Abstract: Objective: Surface electromyogram (EMG) signals have typically been assumed to follow a Gaussian distribution. However, the presence of non-Gaussian signals associated with muscle activity has been reported in recent studies, and there is no general model of the distribution of EMG signals that can explain both non-Gaussian and Gaussian distributions within a unified scheme. Methods: In this paper, we describe the formulation of a non-Gaussian EMG model based on a scale mixture distribution. In the model, an E… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Although the GMM, LDA, and GNB approaches are generative classifiers, similar to the proposed method, they are based on simple Gaussian distributions. Recent studies have suggested that EMG signals follow distributions that are more heavily tailed than Gaussian distributions, which is believed to be due to the variation in EMG variance caused by muscle force changes (Furui et al, 2019b) and muscle fatigue (Furui & Tsuji, 2019). The Gaussian distribution-based classifiers cannot take such variations into account, resulting in relatively low generalization performance.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the GMM, LDA, and GNB approaches are generative classifiers, similar to the proposed method, they are based on simple Gaussian distributions. Recent studies have suggested that EMG signals follow distributions that are more heavily tailed than Gaussian distributions, which is believed to be due to the variation in EMG variance caused by muscle force changes (Furui et al, 2019b) and muscle fatigue (Furui & Tsuji, 2019). The Gaussian distribution-based classifiers cannot take such variations into account, resulting in relatively low generalization performance.…”
Section: Methodsmentioning
confidence: 99%
“…The scale mixture model of surface EMG signals is a stochastic model for raw EMG signals recorded from a pair of electrodes (Furui et al, 2019b). However, EMG pattern classification typically involves the use of EMG signals from multichannel electrodes.…”
Section: Finite Mixture Of Scale Mixture Modelsmentioning
confidence: 99%
See 3 more Smart Citations